Column Chromatography. Issue 13 (1st November 2016) - Chakravarti, Bulbul; Mallik, Buddhadeb; Chakravarti, Deb N.
Abstract: Chromatography is a widely used technique of separation which depends on the differential interaction of molecules between a stationary phase and a mobile phase. In most modern life science laboratories, purification of proteins plays an important role. Almost all types of laboratory‐based liquid chromatography techniques used for purification of proteins are carried out with the stationary phase contained in tubular columns. Although individual methods for sample loading or elution of these columns are usually different depending on the specific technique used, this general experimental procedure that uses tubular columns is known as column chromatography. This unit is focused on setting up laboratory‐based column chromatography methods for separation of proteins using three commonly used chromatographic techniques for separation of proteins, such as size exclusion, ion exchange, and affinity chromatography. © 2016 by John Wiley & Sons, Inc.